Belly-rippers, surgical innovation and the ovariotomy controversy (2018)
‘It is…an interesting question to be decided as to why and wherefore a poor little Fallopian tube or withered ovary should possess the power of setting men by the ears’, commented an editorial in the Medical Press and Circular in 1888.1 Looking back to the nineteenth century, historians might be inclined to wonder the same thing. During this time, the ovary, as an object of physiological and pathological enquiry, and as a site of surgical intervention, engendered more debate and controversy within the profession than any other bodily organ. In the late 1830s, the removal of diseased ovaries, usually those with large non-malignant tumours, became the frst surgical procedure involving major abdominal section to be performed with a degree of regularity, and in 1842, the Manchester surgeon Charles Clay began what was to become a long and unbroken series of operations where he removed the organ. During this decade, the operation was given a name that would be etched on the history of the Victorian era: ‘ovariotomy’, a neologism coined by the Edinburgh obstetrician James Young Simpson in 1843 to describe Clay’s work.